Numerical analysis and optimization of the residual stresses distribution induced by cold expansion technique - Abdelghani Baltach; Abdelkader Djebli; Mostefa Bendouba; El Hadj Besseghier; Abdelkrim Aid (Fracture and Structural Integrity)
This paper presents a numerical investigation about the influence of mandrel shape on residual stresses induced by the cold expansion procedure. Thus, ball and tapered pin are used for cold expanding the plate. As, the entrance face presents the lowest residual stresses throughout the hole thickness, we propose to solve this problem by varying the mandrel taper degree, instead of applying a double expansion. The obtained results show that the tapered pin is more suitable for the cold expansion. More, low taper increases the residual stresses at the entrance, reaching the values generated at the exit face.